2012
DOI: 10.1007/s13691-012-0045-y
|View full text |Cite
|
Sign up to set email alerts
|

UGT1A1*28 and *6 polymorphisms and nilotinib-induced unconjugated hyperbilirubinemia in a Japanese patient with chronic myelogenous leukemia

Abstract: Nilotinib, a second-generation tyrosine kinase inhibitor of BCR-ABL, has shown superior efficacy compared with imatinib for the treatment of chronic myelogenous leukemia (CML). Unconjugated hyperbilirubinemia has been the most frequent adverse event with laboratory abnormality observed in clinical trials of nilotinib. The homozygosity for uridine diphosphate glucuronosyltransferase (UGT) 1A1*28 polymorphism has been reported to increase the risk of nilotinib-induced unconjugated hyperbilirubinemia in Caucasian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…In comparison, only two of the five UGT1A1 NMs experienced high-grade toxicities [ 82 ]. Single patient case reports have described similar findings of severe nilotinib-induced hyperbilirubinemia among UGT1A1 PMs [ 83 , 84 , 85 , 86 ]. Some of the studies identified in our review proposed that UGT1A1 results may help avoid treatment delays and adverse events, but there is a lack of implementation studies assessing UGT1A1 -guided nilotinib prescribing.…”
Section: Resultsmentioning
confidence: 74%
“…In comparison, only two of the five UGT1A1 NMs experienced high-grade toxicities [ 82 ]. Single patient case reports have described similar findings of severe nilotinib-induced hyperbilirubinemia among UGT1A1 PMs [ 83 , 84 , 85 , 86 ]. Some of the studies identified in our review proposed that UGT1A1 results may help avoid treatment delays and adverse events, but there is a lack of implementation studies assessing UGT1A1 -guided nilotinib prescribing.…”
Section: Resultsmentioning
confidence: 74%